Plasma Micronutrient Concentrations Are Altered by Antiretroviral Therapy and Lipid-Based Nutrient Supplements in Lactating HIV-Infected Malawian Women(1)(2)(3) - Flax, Valerie L (J Nutr, 2015)
Background: Little is known about the influence of antiretroviral therapy with or without micronutrient supplementation on the micronutrient concentrations of HIV-infected lactating women in resource-constrained settings. Objective: We examined associations of highly active antiretroviral therapy (HAART) and lipid-based nutrient supplements (LNS) with concentrations of selected micronutrients in HIV-infected Malawian women at 24 wk postpartum. Methods: Plasma micronutrient concentrations were measured in a subsample (n = 690) of Breastfeeding, Antiretrovirals, and Nutrition (BAN) study participants who were randomly assigned at delivery to receive HAART, LNS, HAART+LNS, or no HAART/no LNS (control). HAART consisted of protease inhibitor–based triple therapy. LNS (140 g/d) met energy and micronutrient requirements of lactation. Multivariable linear regression tested the association of HAART and LNS, plus their interaction, with micronutrient concentrations, controlling for season, baseline viral load, and baseline CD4 count. Results: We found significant HAART by LNS interactions for folate (P = 0.051), vitamin B-12 (P < 0.001), and transferrin receptors (TfRs) (P = 0.085). HAART was associated with lower folate (with LNS: −27%, P < 0.001; without LNS: −12%, P = 0.040) and higher TfR concentrations (with LNS: +14%, P = 0.004; without LNS: +28%, P < 0.001), indicating iron deficiency. LNS increased folate (with HAART: +17%, P = 0.037; without HAART: +39%, P < 0.001) and decreased TfR concentrations (with HAART only: −12%, P = 0.023). HAART was associated with lower vitamin B-12 concentrations only when LNS was present (−18%, P = 0.001), whereas LNS increased vitamin B-12 only when no HAART was present (+27%, P < 0.001). HAART, but not LNS, was associated with higher retinol-binding protein (RBP; +10%, P = 0.007). We detected no association of HAART or LNS with selenium, ferritin, or hemoglobin. Conclusion: The association of HAART with lower folate, iron deficiency, and higher RBP plus the attenuation of LNS effects on folate and vitamin B-12 when combined with HAART has implications for the health of lactating HIV-infected women taking HAART in prevention of mother-to-child transmission programs. This trial was registered at clinicaltrials.gov as NCT00164736.